Transcription factor recognition surface on the RNA polymerase alpha subunit is involved in contact with the DNA enhancer element. - Murakami, K (1996)
The carboxy-terminal one-third of Escherichia coli RNA polymerase alpha subunit plays a key role in transcription regulation by a group of protein transcription factors and DNA enhancer (UP) elements. The roles of individual amino acid residues within this regulatory domain of the alpha subunit were examined after systematic mutagenesis of the putative contact regions (residues 258-275 and 297-298) for the cAMP receptor protein (CRP). The reconstituted RNA polymerases containing the mutant alpha subunits were examined for their response to transcription activation by cAMP-CRP and the rrnBP1 UP element. Mutations affecting CRP responsiveness were located on the surface of the putative CRP contact helix and most of these mutations also influenced the response to the rrnB UP element. These observations raise the possibility that the CRP contact surface is also involved in contact with the DNA UP element, although some amino acid residues within this region play different roles in molecular communication with CRP and the UP element. Among the amino acid residues constituting the contact surface, Arg265 was found to play a major role in response to both CRP and the DNA UP element. Judged by DNase I footprinting analysis, alpha mutants defective in transcription from the CRP-dependent lacP1 promoter showed decreased activity in the cooperative binding of CRP. Likewise, mutants defective in rrnBP1 transcription showed decreased binding to the UP element. The amino acid residues important for contact with both CRP and DNA are conserved in the alpha subunits of not only bacterial, but also chloroplast RNA polymerases.